Educational Game Using Android Assisted by Adobe Flash to Improve Learning Interest of Fifth Grade Elementary School Students - Putu Mahadipta; I Made Suarjana; Ni Luh Ika Windayani (Jurnal Media dan Teknologi Pendidikan, 2025)
Mathematics learning should be designed more innovatively through engaging and interactive media. The low student interest, particularly in fractions often perceived as difficult and tedious, highlights the need for learning media that provide a more enjoyable learning experience. This study aims to analyze the development process, feasibility, and effectiveness of an Android-based educational game in enhancing students’ interest in learning fraction addition. The research employed a research and development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included media experts, material experts, teacher practitioners, and elementary school students as the primary users of the media. Data were collected through interviews, observations, literature reviews, tests, and questionnaires, and analyzed using descriptive quantitative and qualitative methods. The findings reveal that the developed learning media demonstrated a high level of validity, featuring attractive visual design, communicative language, and strong alignment between content and learning objectives. Furthermore, the media was considered practical, user-friendly, and effective in creating an active and enjoyable learning atmosphere. In terms of effectiveness, the use of the Android-based educational game successfully increased students’ interest and active participation in learning. These findings suggest that integrating game elements into Mathematics learning can serve as an effective strategy to foster students’ intrinsic motivation and promote meaningful, contextual, and concept-oriented learning experiences.